2011
DOI: 10.1016/j.annepidem.2011.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Life Course Models of Socioeconomic Position and Cardiovascular Risk Factors: 1946 Birth Cohort

Abstract: Purpose To identify the life course model that best describes the association between life course socioeconomic position (SEP) and cardiovascular (CVD) risk factors [body mass index (BMI), systolic and diastolic blood pressure, total cholesterol, low-density lipoprotein, high-density lipoprotein, triglycerides, glycated haemoglobin] and explore BMI across the life course as mediators of the relationship. Methods The Medical Research Council (MRC) National Survey of Health and Development was used to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
98
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(109 citation statements)
references
References 54 publications
8
98
3
Order By: Relevance
“…Early childhood and adolescence in particular are emerging as important periods for the establishment of obesity and programming of cardio-metabolic risk. It has recently been shown in the MRC National Survey of Health and Development that socioeconomic disadvantage in early childhood, more so than at any other age, is associated with cardio-metabolic risk factors at age 53 years, for example (Murray et al 2011). In the same cohort, exposure to obesity emerges during adolescence as being associated with greater carotid-intima media thickness at 60-64 years of age in men ).…”
Section: Critical Periods and Transitionsmentioning
confidence: 99%
“…Early childhood and adolescence in particular are emerging as important periods for the establishment of obesity and programming of cardio-metabolic risk. It has recently been shown in the MRC National Survey of Health and Development that socioeconomic disadvantage in early childhood, more so than at any other age, is associated with cardio-metabolic risk factors at age 53 years, for example (Murray et al 2011). In the same cohort, exposure to obesity emerges during adolescence as being associated with greater carotid-intima media thickness at 60-64 years of age in men ).…”
Section: Critical Periods and Transitionsmentioning
confidence: 99%
“…1,12,13 Childhood and adult SEP independently and jointly contribute to an increased prevalence of CVD risk factors, subclinical disease, and CVD disparities. [14][15][16][17][18][19][20][21] Prior work has also shown that lower cumulative life course SEP was associated with increased prevalence of subclinical CVD 17,[22][23][24] among relatively smaller or non-African American samples.…”
Section: Introductionmentioning
confidence: 99%
“…25 Studies of mostly White populations have shown that early exposure to CVD risk factors may contribute to the development of subclinical CVD as an adolescent, young adult, and adult. [19][20][21]23,24,26 However, it remains uncertain whether the childhood social and economic circumstances of African American adults are related to greater prevalence of subclinical CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Any life course model which offers a model fit as good as the saturated model is then considered further. Since its proposal, the structured life course approach has been applied in several studies exploring the influence of social circumstances on health across the life course (Birnie, et al 2011;Cooper, Mishra & Kuh, 2011;Gustafsson, Persson & Hammarstrom, 2011;Murray et al, 2011;West et al, 2012 ;Wills, Hardy, Black & Kuh, 2010) and throughout childhood (Evans & Kohli, 1997;Giles et al, 2011;Lin, Leung, Hui, Lam and Schooling, 2011).…”
Section: Introductionmentioning
confidence: 99%